(untitled) (Impetus, 2021)
The aim of this reflection paper is to present some of the cultural and identity characteristics and features of children’s literature related to Physical Education and Sports in Brazil and in Spain. For this, a set of works on the subject has been compiled. This study revealed valuable information about cultural characteristics and identity traits common to the societies of the referred countries through children’s literature. In addition, it can be seen that children’s books published in Brazil and in Spainhave much more similarities than differences. Finally, it should be noted that football is the predominant subject in children’s works in both countries. By way of reflection, the following questioning is established: since football is a sport commonly practiced by Brazilian and Spanish children, why do the teachers of these two countries not use these children’s works in Physical Education classes?